Projeto Terapêutico Singular (PTS): as percepções dos trabalhadores de um Centro de Atenção Psicossocial Álcool e Drogas (CAPS ad) - Cadore, Carlise (2012)
The Health and Psychiatric Reform movements in Brazil triggered transformations in theoretical and practical model of mental health care. These changes enabled the expansion of the concept of health / disease process, the creation of public policies, the implementation of a network of services replacing psychiatric hospitals, including the CAPS and the development of new strategies for health intervention. Therefore, these changes suggest a series of challenges to the practice of workers in health services, especially with regard to care and care for people in psychological distress, using as a framework the assumptions of the fields of Public Health and Mental Health. So the overall goal of this research was to describe and analyze how health workers of a Psychosocial Alcohol and Drugs Care Center (CAPS ad), build, lead and propose therapeutic processes of users in that service. It interested us especially to understand how in this process the development of Singular Therapeutic Projects (STP) occurs. From this perspective, considering that the therapeutic process is conducted in a CAPS resulting from conceptions and modes of action of different workers who make up the staff of such services, justified the choice of the theme by the need to describe and analyze the actions of these health workers as a way to discuss their practice, pointing out the obstacles and difficulties in the construction and conduct of therapeutic processes, as well as point out possible solutions to these issues. Thus, an exploratory-descriptive survey was conducted, with qualitative approach. For data collection, interviews were conducted semi-structured with seven workers of different specialties working in CAPS ad. Data analysis was performed according to thematic analysis proposed by Minayo. The results demonstrate that the conceptions of workers in relation to the therapeutic process are consistent with the principles and guidelines of the Psychiatric Reform and the Current Mental Health Policy and the construction of the Singular Therapeutic Project (STP), generally occurs according to the proposal of the Ministry of Health. We believe that STP could be used in the searched service as a production strategy of health care.